A Historical Analysis of the Central American Non-criminal Mechanisms for Colombia - Ulrich, William Eugene (DIXI, 2017)
Purpose: This article proposes a historical-comparative approach to the history, development and forms of solutions implemented by Guatemala, El Salvador and Nicaragua in the internal conflicts they experienced in the eighties and nineties, and a comparison is made with the end of the conflict between Colombia and farc. Description: The irregular nature of Central American conflicts and their immense similarity with the conflict in Colombia—which, like them, faced an organized guerrilla—allow for an analysis to observe historical events critically and bring them to a present in which experiences are repeated almost inevitably. Point of view: Central American conflicts offer an excellent opportunity for analysis for the current work since their striking resemblance to the Colombian conflict provides a considerable amount of material that must be taken into consideration and many proposals that cannot be ignored. Conclusions: It is necessary to present various cases and experiences to extract the necessary learning and not repeat the mistakes made in the past.